HUMANITIES STUDIES AS AN ATTRIBUTE FOR EDUCATIONAL INNOVATION - Alexander A. Polonnikov; Galina N. Prozumentova (Высшее образование в России)
This is a methodological review of a case study discourse in humanities teaching; the focus is on the role and significance of scientific methods in the practices of reproduction and development of education. The heuristic value of the case study is demonstrated, followed by a discussionof the educational prerequisites for the application of the casestudy procedure and the use of its results inpredicting educational change. The aim was to develop an operating framework for supervisors and academic advisors to practitioners of innovative methods of education and students of a variety of education-related issues.